2021
DOI: 10.15561/10.15561/26649837.2021.0101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of six-week slow, controlled breathing exercises on heart rate variability in physically active, healthy individuals

Abstract: Background and Study Aim: Heart rate variability (HRV) provides information about sympathetic-parasympathetic balance. The effects of different types of physical exercises on HRV have been investigated so far. The purpose of the current study was to evaluate the chronic effects of six-week slow and controlled breathing exercise on HRV in physically active, healthy adults. Material and Methods: A total of 22 individuals (11 female, 11 male) participated in the study voluntarily. The experimental group (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tharion et al (2012) found that individuals practicing breathing at 6 breaths per minute for 1 month experienced decreased resting breathing rate and increased resting HF HRV. Sürücü et al (2021) found increased HF and LF HRV and an increased LF/HF ratio in healthy adults that practiced 6 breaths per minute breathing. Van Diest et al (2014) also determined that breathing at 6 breaths per minute leads to higher HRV than 12 breaths per minute.…”
Section: Introductionmentioning
confidence: 80%
“…Tharion et al (2012) found that individuals practicing breathing at 6 breaths per minute for 1 month experienced decreased resting breathing rate and increased resting HF HRV. Sürücü et al (2021) found increased HF and LF HRV and an increased LF/HF ratio in healthy adults that practiced 6 breaths per minute breathing. Van Diest et al (2014) also determined that breathing at 6 breaths per minute leads to higher HRV than 12 breaths per minute.…”
Section: Introductionmentioning
confidence: 80%
“…Although baseline RSA has been implicated in developmental outcomes related to children's allostatic load (Hinnant et al., 2013), it is unclear whether interventions could alter baseline RSA in children. Recent evaluations of breathing interventions revealed that 4 or 6 weeks of brief weekly breathing exercises can yield significant increases in baseline RSA levels in small adult samples (Lin, 2018; Sürücü et al., 2021) and decreases in HR in adolescents (Gregoski et al., 2011). Future research should extend this work to children and examine whether regular deep breathing practice can have a sustained effect on baseline RSA levels.…”
Section: Discussionmentioning
confidence: 99%